Two men outside A. Dinkelspiel's Alaska Outfitting Company, Nome, probably between 1899 and 1900 - Warner, Arthur Churchill, 1864-1943 (1899)
Gold was discovered on the Nome beaches in the Summer of 1899. By Spring of 1900, thousands had arrived for the gold rush. Adolph Dinkelspiel and his brother Joseph were born in Germany in 1848 and 1845, respectively. In 1900, Joseph was running the Dinkelspiel store in Nome, while Adolph lived in Seattle with his family. By 1910, both Adolph and Joseph had died, and Adolph's widow, Bella, was head of household in Seattle. [Source: U.S. Census] Warner 106 Filed in Alaska series.